Cooperation Between Law Enforcement Agencies of Ukraine and The Republic of Poland in Countering Criminal Election Offenses During Ukrainian External Voting, Committed Outside the Diplomatic Institutions of Ukraine in Post-War Conditions - Paliukh, Lidiia; Kaluzhna, Oksana (PRAWO i WIĘŹ, 2024)
The paper deals with the current legal issues of law enforcement agencies’ cooperation during the criminal proceedings on election offences committed during the Ukrainian elections on the territory of the Republic of Poland. The article focuses on the most problematic situations when an election criminal offence is committed outside the territory of a diplomatic institution of Ukraine. Gaps in the legal regulation are identified, as well as issues that need to be additionally regulated in the agreement between Ukraine and the Republic of Poland on cooperation in the organization and conduct of Ukrainian elections in order to prevent election offences.